The Literacy of Elementary School Students on Food and Environmental Sustainability Values in Local Wisdom - Sumarwati; Anindyarini, Atikah; Suryanto, Edy; Hadiyah; Muftihah, Nani; Alfien, Moh. Fajrul (Universitas Pendidikan Ganesha, 2024)
The low awareness among the younger generation regarding the values of food and environmental sustainability poses a significant challenge in preserving cultural heritage and ecosystems in Indonesia. This study aims to describe the level of students' literacy on food and environmental sustainability values embedded in their local wisdom. The study involved 252 sixth-grade students as participants. Data were collected through surveys and interviews to assess the students' understanding of food sustainability values in folktales, such as the origins of vegetables and corn, and environmental sustainability values in traditional ceremonies, such as the village clean-up ceremony and water source conservation. The data were analyzed using both quantitative and qualitative approaches to provide a comprehensive understanding of the students' literacy. The findings revealed that the majority of students showed more positive literacy regarding environmental sustainability values in traditional ceremonies compared to food sustainability values in folktales. Students were more supportive of environmental cleanliness and the preservation of water sources. On the other hand, students' literacy regarding food sustainability values, particularly those related to corn, was relatively low. Key factors influencing this low literacy included limited access to folktales, negative perceptions of corn-based foods (which are associated with